FIELD TEST OF THE INDIGENOUS MICROBES FOR OIL RECOVERY, LEDOK FIELD, CENTRAL JAVA - A. Yusuf; S. Kadarwati; S.W. Pratomo (Scientific Contributions Oil and Gas, 2002)
After selecting several old wells in Cepu, then well LDK-132 was chosen for implementing MEOR technology using "huff and puff" method. For this purpose, fluids samples (water and oil) from Ledok Formation were taken at the wellhead. No core of LDK-132 was available, only cores from LDK-209 and LDK-P1 were found. Core plugs could not be made from the former due to compacted and tightly conditions with a very low permeability of only 0.458 md. The latter with the permeability of 140 md met the requirements of microbial core flooding (MCF) tests, A standard quartz dominated core from Clashach Scotland with permeability almost 800 md was also used to compare with the native core's results. The MCF tests were conducted at the reservoir conditions for both types of core. The native core gave a recovery factor of oil production of 12.58%, while the standard core yielded a higher recovery fac- tor of 21.22% of Sor. Based on these results, the MEOR implementation was conducted on July 8, 1999 by injecting 135 barrels of mixtures consist- ing of formation water, microbes enriched with KKL-11 (Koleksi Kultur Lemigas or Lemigas Cultures Collection) and M4 medium through the annulus of LDK-132. The result showed an increase of average oil production rate, from 3.46 bopd, 6 days before the injection, to 24.85 bopd, 6 days after the injection.